Narrative Literature Review of Potential Atrial Fibrillation Mechanism of Action Induced by Discontinuation of Benzodiazepines - Okulevičiūtė, Agnė; Laubner Sakalauskienė, Gabija (Acta medica Lituanica, 2023)
Introduction: Benzodiazepines are commonly prescribed but often misused, leading to dependence and withdrawal symptoms. Increased worldwide prescriptions raise adverse effects and overdose concerns, especially for the elderly. Caution is needed in prescribing and considering alternative treatments to minimize risks. Aim: Narrative literature review of potential atrial fibrillation mechanism of action induced by discontinuation of benzodiazepines. Materials and methods: Database PubMed was searched using the combination of keywords – “Benzodiazepine AND atrial fibrillation OR peripheral benzodiazepine receptors”, “history of benzodiazepines”, “benzodiazepines mechanism of action”, “benzodiazepines indications”, “benzodiazepines adverse effects” and “benzodiazepines withdrawal effects”. Non-full-text and non-English scientific publications were removed. A total of 31 publication was included. Discussion: Benzodiazepines (BZDs) were synthesized in 1955 and initially considered less toxic than barbiturates. They interact with GABA-A receptors, causing hyperpolarization and inhibitory effects in the central nervous system. BZDs are used to treat various clinical disorders, but long-term use can lead to adverse effects and withdrawal symptoms. There is evidence that genetic diversity can influence the response to BZDs through GABA receptors. The interaction between benzodiazepines and peripheral benzodiazepine receptors may influence calcium ion channels, affecting cardiac action potential and contractility, and discontinuation of these medications can potentially contribute to atrial fibrillation. Additionally, benzodiazepines may directly affect calcium channels, causing antiarrhythmic effects and vasodilation. Conclusion: In summary, benzodiazepines, once considered safer sedatives, now raise concerns about misuse, dependence, and withdrawal symptoms. While there is a potential link between discontinuing benzodiazepines and atrial fibrillation through mechanisms involving peripheral benzodiazepine receptors and cardiac calcium channels, causality remains uncertain and multifaceted. Further research is needed to clarify these mechanisms, and healthcare providers should exercise caution in long-term benzodiazepine prescriptions while exploring alternative treatment strategies to mitigate risks.